Comparison of health-related quality of life between patients with different metatarsalgia types and matched healthy controls: a cross-sectional analysis - Tovaruela-Carrión, Natalia; López-López, Daniel; Losa-Iglesias, Marta Elena; Álvarez-Ruíz, Verónica; Melero-González, Gemma; Calvo-Lobo, César; Bengoa-Vallejo, Ricardo Becerro-de (São Paulo Medical Journal, 2018)
BACKGROUND: Metatarsalgia can be considered to be a common complaint in clinical practice. The aim of this study was to compare quality of life (QoL) between participants with different metatarsalgia types and matched-paired healthy controls. DESIGN AND SETTING: A cross-sectional analysis on a sample of 124 participants of median age ± inter- quartile range of 55 ± 22 years was carried out in the University Clinic of Podiatric Medicine and Surgery, Ferrol, Spain. They presented primary (n = 31), secondary (n = 31) or iatrogenic (n = 31) metatarsalgia, or were matched-paired healthy controls (n = 31). METHODS: Self-reported domain scores were obtained using the Foot Health Status Questionnaire (FHSQ) and were compared between the participants with metatarsalgia and between these and the healthy controls. RESULTS: Statistically significant differences were shown in all FHSQ domains (P ≤ 0.001). Post-hoc anal- yses showed statistically significant differences (P < 0.05) between the metatarsalgia types in relation to the matched healthy control group, such that the participants with metatarsalgia presented impaired foot-specific and general health-related QoL (lower FHSQ scores). CONCLUSION: This study demonstrated that presence of metatarsalgia had a negative impact on foot health-related QoL. Foot-specific health and general health were poorer among patients with metatarsal- gia, especially among those with secondary and iatrogenic metatarsalgia, in comparison with matched healthy controls.